Critical decisions in higher education. The proceedings of the 18th annual National Conference on Higher Education, March 3-6, 1963. Editor: G. Kerry Smith. Assistant editors: E.N. Shiver [and] Th.A. Erhard (Association for Higher Education, a department of the National Education Association, 1963)
With indices. Current issues in higher education, 1963.